Neuropsychological Functioning in Older Adults with Mild Cognitive Impairment and Insomnia Randomized to CBT-I or Control Group. Issue 2 (15th March 2018) - Cassidy-Eagle, Erin; Siebern, Allison; Unti, Lisa; Glassman, Jill; O'Hara, Ruth
ABSTRACT: Objectives : Improving the sleep of older adults with mild cognitive impairment (MCI) represents a first step in discovering whether interventions directed at modifying this risk factor also have the potential to alter the cognitive decline trajectory. Methods : A six-session, adapted version of a cognitive behavioral therapy for insomnia (CBT-I) was administered to older adults (N = 28; 14 per group) with MCI across two residential facilities. Participants were randomly assigned to either the sleep intervention or an active control group and completed a neuropsychological battery at three time points (e.g., baseline-T1, post-intervention-T2, 4 month follow-up-T3). Results : Results showed a significant improvement in sleep and a change ( p  < .05) on a key measure of executive functioning sub task of inhibition (Condition 3 of D-KEF Color-Word Interference Test), a positive trend on the inhibition-switching task ( p  < .10; Condition 4 of D-KEF Color-Word Interference Test), an no change in a measure of verbal memory (HVLT-R Delayed Recall) compared with the active control group. Conclusions : CBT-I is a nonpharmacological intervention that has the potential to cognitively benefit individuals with MCI suffering from comorbid insomnia. Clinical Implications : Results suggest that a non-pharmacological intervention to improve sleep in older adults with MCI also improve cognitive functioning. Further exploration of the mechanisms underlying these improvements is warranted.